2008
DOI: 10.1093/annonc/mdn166
|View full text |Cite
|
Sign up to set email alerts
|

Randomized phase III study comparing irinotecan combined with 5-fluorouracil and folinic acid to cisplatin combined with 5-fluorouracil in chemotherapy naive patients with advanced adenocarcinoma of the stomach or esophagogastric junction

Abstract: IF did not yield a significant TTP or OS superiority over CF, and the results of noninferiority of IF were borderline. However, IF may provide a viable, platinum-free front-line treatment alternative for metastatic gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
165
0
12

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(188 citation statements)
references
References 32 publications
11
165
0
12
Order By: Relevance
“…The first phase II study results suggested that irinotecan and 5-fluorouracil combinations had promising antitumoral activity and efficacy [49,50]. A randomized controlled phase III trial failed to show the superiority of irinotecan and high-dose 5-fluorouracil over only cisplatin and 5-fluorouracil [51]. However, quality of life tended to be better during treatment with irinotecan and 5-fluorouracil.…”
Section: Irinotecan-containing Regimensmentioning
confidence: 99%
“…The first phase II study results suggested that irinotecan and 5-fluorouracil combinations had promising antitumoral activity and efficacy [49,50]. A randomized controlled phase III trial failed to show the superiority of irinotecan and high-dose 5-fluorouracil over only cisplatin and 5-fluorouracil [51]. However, quality of life tended to be better during treatment with irinotecan and 5-fluorouracil.…”
Section: Irinotecan-containing Regimensmentioning
confidence: 99%
“…Three randomized trials tested treatment combinations of infused 5-FU and irinotecan [7,17,18]. A phase III trial randomized 333 patients to irinotecan plus high-dose 5-FU and leucovorin (IF) or cisplatin and 5-FU (CF).…”
Section: Discussionmentioning
confidence: 99%
“…The IF regimen was not superior over CF for time to progression (5.0 versus 4.2 months), median OS time 9.0 versus 8.7 months, or RR 31.8% versus 25.8%, but showed a better safety profile: in fact, while increased rate of grade 3-4 diarrhoea was reported with IF, the incidence of grade 3-4 stomatitis and haematological toxicity, in particular neutropenic fever, was significantly lower. [7]. According to a meta-analysis, irinotecan regimens show a non-statistically significant benefit in survival of about 1 month and a lower rate of treatment-related deaths over the reference regimen [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IFF regimen produced a greater response rate (RR) (32 vs. 25%), and demonstrated a marginally signiWcant superior progression-free survival (PFS) (5.0 vs. 4.2 months, P = 0.088), but not overall survival (OS) (9.0 vs. 8.7 months) in comparison with the reference regimen, showing a better toxicity proWle [14].…”
Section: Introductionmentioning
confidence: 99%